Anesthetic considerations for a pediatric patient with Wolf-Hirschhorn syndrome: a case report - Tsukamoto, Masanori (J Dent Anesth Pain Med, 2017)
Wolf-Hirschhorn syndrome is a rare hereditary disease that results from a 4p chromosome deletion. Patients with this syndrome are characterized by craniofacial dysgenesis, seizures, growth delay, intellectual disability, and congenital heart disease. Although several cases have been reported, very little information is available on anesthetic management for patients with Wolf-Hirschhorn syndrome. We encountered a case requiring anesthetic management for a 2-year-old girl with Wolf-Hirschhorn syndrome. The selection of an appropriately sized tracheal tube and maintaining intraoperatively stable hemodynamics might be critical problems for anesthetic management. In patients with short stature, the tracheal tube size may differ from what may be predicted based on age. The appropriate size ( internal diameter ) of tracheal tubes for children has been investigated. Congenital heart disease is frequently associated with Wolf-Hirschhorn syndrome. Depending on the degree and type of heart disease, careful monitoring of hemodynamics is important.